Exploring the musical taste of expert listeners: musicology students reveal tendency toward omnivorous taste - Elvers, Paul; Omigie, Diana; Fuhrmann, Wolfgang; Fischinger, Timo (Frontiers in Psychology, 2015)
The current study examined the musical taste of musicology students as compared to a control student group. Participants (n=1003) completed an online survey regarding the frequency with which they listened to 22 musical styles. A factor analysis revealed six underlying dimensions of musical taste. A hierarchical cluster analysis then grouped all participants, regardless of their status, according to their similarity on these dimensions. The employed exploratory approach was expected to reveal potential differences between musicology students and controls. A three-cluster solution was obtained. Comparisons of the clusters in terms of musical taste revealed differences in the listening frequency and variety of appreciated music styles: The first cluster (51% musicology students / 27% controls) showed the greatest musical engagement across all dimensions although with a tendency towards »sophisticated« musical styles. The second cluster (36% musicology students / 46% controls) exhibited an interest in »conventional« music, while the third cluster (13% musicology students / 27% controls) showed a strong liking of rock music. The results provide some support for the notion of specific tendencies in the musical taste of musicology students and the contribution of familiarity and knowledge towards musical omnivorousness.